Maintaining Civic Space: Women Activist and Spatial Politics During Pandemic Covid-19 in Indonesia - Robertus Robet; Retna Hanani; Charine Charine (Yayasan Jurnal Perempuan, 2020)
The Covid19 pandemic has changed society's spatial practices substantially. Large-scale social restrictions, lockdowns, and the obligation to wear masks have changed the way humans relates to each other personally and politically. This article discusses how the pandemic has shaped civic space of women activists and how women activists maintain and create civic space amid the pandemic and democratic regression. The data source of the article is collected through online survey of 20 women activists and in-depth online interviews. The results show that civil society organizations in Indonesia are under immense pressure due to pandemic and democratic regression. For civil society organizations, their space is limited by various legal regulations and various violence and stigma aimed at civil society activists. More than that, for women activists the pandemic also provides additional domestic burdens which make the space for women activists increasingly limited. In the midst of these obstacles, our research shows that women and civil society activists do not reduce their intensity in maintaining the civic space.